Necessary nonsense : aesthetics, history, neurology, psychology - Massey, Irving (Columbus : The Ohio State University Press, 2018)
"This book explores the cognitive possibilities of nonsense, literary and philosophical--ranging from Immanuel Kant to Lewis Carol, from examinations of Asperger's Syndrome to the waking state--and demonstrates that there is an element of nonsense, or stage of nonsense, in the normal course of thought"--
Nonsense: usage and uses -- Metaphor and nonsense -- The baroque: nonsense in prospect and retrospect -- Salutary nonsense: Keats, Kant, and Madame de Staël; or inspiration vs. fanaticism -- Neural nonsense: neuroaesthetics, hypnagogia, and the aesthetics of nonsense -- Perceptual nonsense: the "image made by chance," automaticity, and the aesthetic universal -- Assorted nonsense.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed November 5, 2018).
JSTOR
Keywords: Nonsense literature -- History and criticism; Literature -- Aesthetics; Literature -- Psychology; Littérature nonsensique -- Histoire et critique; Littérature -- Esthétique.; Littérature -- Psychologie; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- General; Literature -- Aesthetics; Literature -- Psychology; Nonsense literature; Electronic books; Criticism, interpretation, etc